Early Clinical Experience of Gamma-AP Nailing with Fluoro-Navigation - Leung, K. S.; Tang, N.; Yue, W. (Osteosynthesis and Trauma Care, 2005)
This is a report on the early experience of the application of fluoro-navigation in Gamma nail fixation of the peritrochanteric fractures. With the newly designed adapters that are attached to the standard Gamma nail instruments, the surgery can be done with fluoro-navigation guidance for the entry of the medullary canal, nail insertion, lag screw insertion as well as the distal locked screw insertion. The early results of fixing 28 peritrochanteric fractures are encouraging. The average duration of surgery was 42 min, the average number of X-ray screening during navigation was 10.5. The average wound length was 8.21 cm. No complication was recorded during surgery and after surgery. This report confirms the feasibility of the application of fluoro-navigation in Gamma nailing with the advantages of decreasing X-ray exposure and accurate implant position. The surgical trauma is further decreased with smaller incisions. Further improvement in the surgical technique and precautions are also discussed.
Keywords: Gamma nail; fluoro-navigation; minimally invasive surgery